Why and how teachers make use of drawing activities in early childhood science education. Issue 13 (2nd September 2021) - Areljung, Sofie; Due, Karin; Ottander, Christina; Skoog, Marianne; Sundberg, Bodil
ABSTRACT: Researchers have provided many arguments for why drawing may contribute to science learning. However, little is known about how teachers in early childhood education (ECE) make use of drawing for science learning purposes. This article examines how teachers' views and framing of drawing activities influence the science learning opportunities afforded to children in the activities. We use activity theory to analyse teacher interviews and observation data from ten science classrooms (children aged 3–8 years) where drawing activities occurred. The interviews reveal that few of the teachers relate drawing to science learning specifically. Rather, they portray drawing as a component of variation in teaching and learning in general. Looking at what happens in the classrooms, we conclude that drawing has a relatively weak position as means of communicating and learning science. Instead, the teaching emphasis is on writing or on 'making a product'. However, there are examples where teachers explicitly use drawing for science learning purposes. These teachers are the same few who, in interviews, relate drawing to science learning specifically. Based on these findings, we encourage school teachers, teacher educators, and researchers to identify, and overcome, obstacles to realising the pedagogical potentials of drawing in ECE science classrooms.